The ethics of placebos - Donna Knapp van Bogaert; Gboyega A. Ogunbanjo (South African Family Practice)
The word “placebo”, first used during funeral ceremonies in the 14th century, is derived from old Latin and means “I shall please”. At the time, it was practice among Roman Catholics to hire professional mourners to wail vespers for the dead. Placebo Dominio regione vivorium translates from Psalm 116: 9 as “I shall please the Lord in the land of the living”. Professional mourners served as stand-ins for the family of the deceased. They “walked” before the holy being by acting in a manner which pleased Him. Over time and in many circles, the term came to connote a substitution for the actual.